Antimicrobial Resistance Profiling of Escherichia coli Isolated from Chickens in Northern Province of Rwanda. (2022)
Antimicrobial resistance (AMR) is a global public health concern due to inappropriate antimicrobial-use in humans and animals including poultry. Escherichia coli have been proposed as one of the pathogens to be used for AMR surveillance. The goal of current study was to determine the antimicrobial resistance of E. coli in chickens in Northern Province of Rwanda. A cross- sectional study was conducted between June and August 2021; the chickens were randomly selected in each of the twenty farms that were included in the study. The samples were collected from cloaca and from farm environment. E. coli was isolated and identified and antimicrobial susceptibility testing was done using disc diffusion method. The results were defined as resistance(R), susceptible(S) and intermediate (I). After Data processing, they were entered in Microsoft Excel for analysis. The data were presented as frequencies and percentages. In total, 384 samples were collected (139 in Gakenke, 114 in Rulindo and 131 in Musanze Districts). E. coli was isolated from 162(42.18%) among which 40 (24.7%) were from Musanze District, 57(35.2%) from Gakenke District and 65 (40.1%) were from Rulindo District. The highest resistance was observed for tetracycline (69.8%) followed by cotrimoxazole (39.5%). The highest susceptibility was observed for gentamycin (100%) followed by ciprofloxacin (96.9%) and amoxicillin (66%). This study indicated the presence of E. coli in chickens of Northern Province of Rwanda and a large number of antibiotic resistant E. coli were isolated. Therefore, the government should set policies to control the use of antibiotics on farms.